Development of guided DIY system with augmented reality - Ho, Don Jun Le (2017)
Augmented Reality can be defined as the interaction between virtual objects and the real world. In order for Augmented Reality to be realized, virtual objects have to be superimposed into the reality through equipment such as the camera. In recent times, AR technologies has constantly been implemented to software applications to provide a whole new experience of immersion and interactivity to users. In this report, AR technology would be implemented in a Guided “Do It Yourself” (DIY) system as part of a holistic approach in the development of the system. A web-based platform will provide users with the tools to view user generated guide, create, edit and delete guides of their own. These user generated guides would then be retrieved on mobile platforms through an AR application developed for the IOS and Android devices for display and use. VR headwear can be used to further enhance the immersive and interactive experience of the application. In adapting this holistic approach, the system aims to provide users with a seamless DIY experience that is interactive and at the same time, effectively and efficiently aiding users in assembling/constructing/handling their DIY products of any categories.